The social integration process of highly skilled immigrant mothers and the intergenerational legacy. A case study of Denmark reality - Marta Ortega-Gaspar; Marta Juarez-Peña (University of Bologna, 2022)
Social integration process of immigrants has long been a key issue in the government agenda. This study analyzes the barriers and strategies for professional integration of highly skilled immigrant mothers during the process of immersion in a new social and cultural environment. The analysis allows the understanding of how these women recover a professional status lost during the migratory process and how they achieve a balance between the different roles they play in the host danish society. Qualitative research has been carried out through semi-structured interviews to highly skilled professional women settled down in Denmark. Results suggest that immigrant women make a series of concessions in exchange for a series of advantages, which according to interviewees are gender security and equality. It is observed the importance they attach to the values they hope to instill in their children. Their endeavor will be worth it, in the sense that in Denmark they will find stability and security for their family, for themselves, and especially for their children.